2022
DOI: 10.1136/emermed-2020-210628
|View full text |Cite
|
Sign up to set email alerts
|

The association between vital signs and clinical outcomes in emergency department patients of different age categories

Abstract: BackgroundAppropriate interpretation of vital signs is essential for risk stratification in the emergency department (ED) but may change with advancing age. In several guidelines, risk scores such as the Systemic Inflammatory Response Syndrome (SIRS) and Quick Sequential Organ Failure Assessment (qSOFA) scores, commonly used in emergency medicine practice (as well as critical care) specify a single cut-off or threshold for each of the commonly measured vital signs. Although a single cut-off may be convenient, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
(54 reference statements)
0
18
1
Order By: Relevance
“…Why MEWS was not complete or not recorded at all remains uncertain. Although the authors state that the MEWS was recorded across the entire spectrum of disease severity, in a large multicentre quality registry of the Netherlands,3 we found the number of missing vital signs to be associated with mortality and admission. Excluding observations with incomplete MEWS may therefore have caused considerable selection and information bias and might have been mitigated by reporting missing value proportions or by multiple imputations of missing values following appropriate analyses, as recommended by TRIPOD 2.…”
contrasting
confidence: 57%
“…Why MEWS was not complete or not recorded at all remains uncertain. Although the authors state that the MEWS was recorded across the entire spectrum of disease severity, in a large multicentre quality registry of the Netherlands,3 we found the number of missing vital signs to be associated with mortality and admission. Excluding observations with incomplete MEWS may therefore have caused considerable selection and information bias and might have been mitigated by reporting missing value proportions or by multiple imputations of missing values following appropriate analyses, as recommended by TRIPOD 2.…”
contrasting
confidence: 57%
“…The different baseline characteristics (especially the average age, ICU admission rates, and mortality rates) of the derivation cohorts and differences in epidemiological conditions (e.g., healthcare systems, need for triage) might be the reason for differences of performance in our cohort. It has been demonstrated before that the impact of changing vital sign categories on prognosis in terms of mortality is larger in older patients [23]. This can be especially discussed for the derivation cohort of COVID-GRAM with a mean age of 48.9 years in comparison with our cohort with a mean age of 65 years.…”
Section: Discussionmentioning
confidence: 52%
“…However, the study did not report clear cut-off points for SBP, DBP, SpO 2 , or heart rate and did not provide AORs for mortality. The AOR for RR gradually increased between 10 and 19 breaths/min with a substantial increase in mortality at 22 breaths/min [ 16 ]. Tringali et al’s study reported that DBP values below 70 mmHg were associated with increased all-cause mortality in patients aged 45 years or older who encountered outpatient care [ 17 ].…”
Section: Discussionmentioning
confidence: 99%